2017
DOI: 10.1180/minmag.2016.080.158
|View full text |Cite
|
Sign up to set email alerts
|

On the nature and origin of garnet in highly-refractory Archean lithospheric mantle: constraints from garnet exsolved in Kaapvaal craton orthopyroxenes

Abstract: The widespread occurrence of pyrope garnet in Archean lithospheric mantle remains one of the 'holy grails' of mantle petrology. Most garnets found in peridotitic mantle equilibrated with incompatible-trace-element enriched melts or fluids and are the products of metasomatism. Less common are macroscopic intergrowths of pyrope garnet formed by exsolution from orthopyroxene. Spectacular example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 105 publications
(175 reference statements)
3
11
0
1
Order By: Relevance
“…Similar exsolved samples have previously been described from the SCLM (Aoki et al, 1980, Dawson, 2004, Dawson et al, 1980, Gibson, 2017, but what is significant about BP002 is the visible physical disintegration of the megacryst into the main body of the xenolith. Several observations suggest that garnet and orthopyroxene throughout the granular portion of sample BP002 likely originated from structural break-up of exsolved orthopyroxene-garnet megacrysts: the presence of strained orthopyroxene amongst the relatively unstrained olivine and garnet; the occurrence of garnet inclusions in orthopyroxene; and the identical compositions of the spatial association of garnet and orthopyroxene more generally seen in granular peridotites (Cox et al, 1987, Saltzer et al, 2001).…”
Section: Evidence For Exsolutionsupporting
confidence: 74%
See 1 more Smart Citation
“…Similar exsolved samples have previously been described from the SCLM (Aoki et al, 1980, Dawson, 2004, Dawson et al, 1980, Gibson, 2017, but what is significant about BP002 is the visible physical disintegration of the megacryst into the main body of the xenolith. Several observations suggest that garnet and orthopyroxene throughout the granular portion of sample BP002 likely originated from structural break-up of exsolved orthopyroxene-garnet megacrysts: the presence of strained orthopyroxene amongst the relatively unstrained olivine and garnet; the occurrence of garnet inclusions in orthopyroxene; and the identical compositions of the spatial association of garnet and orthopyroxene more generally seen in granular peridotites (Cox et al, 1987, Saltzer et al, 2001).…”
Section: Evidence For Exsolutionsupporting
confidence: 74%
“…Their model is supported by the spatial relationship between garnet and orthopyroxene (Saltzer et al, 2001) and by experimental phase equilibria (Canil, 1991, Canil, 1992. Examples of garnet exsolution in Cr-rich orthopyroxene megacrysts have been described from several cratons (Aoki et al, 1980, Dawson et al, 1980, Dawson, 2004, Gibson, 2017, Wasch et al, 2009. However, thus far no direct link between these rare exsolved garnet and the distinct grains that occur in granular harzburgite has been convincingly demonstrated.…”
Section: Introductionmentioning
confidence: 92%
“…This roughly coincides with the depth range where cratonic lithosphere displays the highest seismic velocities, in most cases, in southern Africa and elsewhere. Gibson () inferred that the garnet exsolution probably occurred during the lithospheric thickening, possibly during the Archean cratonization; further evidence is needed to establish the timing and mechanisms unambiguously. Seismic data relating to the amplitude and lateral variability of the sub‐Moho increase in VnormalS with depth can help by providing new observational constraints on the composition, with broader inferences on the evolution of the cratons.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of the exsolution and the distribution of garnet depends on the cooling and metasomatic history of the lithosphere (e.g., Saltzer et al, ). Pressure and temperature estimates of Gibson (), obtained from the mantle xenoliths and megacrysts from the Kaapvaal Craton, revealed that the orthopyroxenes with exsolved garnet were entrained from a broad, 85–175 km depth interval. This roughly coincides with the depth range where cratonic lithosphere displays the highest seismic velocities, in most cases, in southern Africa and elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that long before the crystallization of the first newly formed minerals of external origin, the orthopyroxenite system had experienced the solid solution breakdown of the high-T orthopyroxene precursor with the formation of exsolved clinopyroxene and magnesio-chromite, as indicated by the numerous morphologically oriented inclusions of these minerals in enstatite. Clinopyroxene, magnesio-chromite and vein-like garnet grains, which are distributed in subordinate amounts around the enstatite crystals, seem to be of exsolution origin as well, as documented in some global orthopyroxenite occurrences [65,66]. Later, the orthopyroxenite served as a natural substrate for crystallization of various minerals that are united by the fact that they are epigenetic with respect to the host rock and crystallized from passing liquids.…”
Section: The Genesis Of Minerals: Evidence For the Superimposed Naturementioning
confidence: 97%